Modelling and mitigation of storm-induced saltwater intrusion: Improvement of the resilience of coastal aquifers against marine floods by subsurface drainage. (February 2018) - Elsayed, Saber M.; Oumeraci, Hocine
Abstract: Storm-induced saltwater intrusion (SISWI) often starts with (i) overtopping/breaching of a coastal barrier followed by (ii) hinterland inundation and (iii) subsequent vertical seawater intrusion behind the barrier. Though these three processes are naturally successive, they are often analysed separately. However, the necessity of considering these processes as fully coupled has been increasingly recognised. This study, therefore, addresses the modelling of these processes in an integrated approach. The previous related studies are examined and four coupling scenarios are proposed. Thus, a new modelling scenario, utilising the model XBeach for simulating overtopping/breaching and subsequent flooding and SEAWAT for simulating the SISWI, is chosen for application to a case study in northern Germany. Moreover, the study addresses the mitigation of SISWI using a subsurface drainage network. The simulation results illustrate the high efficiency of such drainage in shortening the remediation time as well as in limiting salt intrusion to the deeper freshwater aquifers. Graphical abstract: Highlights: Modelling approaches for storm-induced saltwater intrusion are presented. New approach utilises XBeach and SEAWAT is presented to simulate vertical intrusion. The proposed model is applied to a case study in northern Germany. Subsurface drainage is simulated to shorten remediation time of polluted aquifers.